Identification of putative Cof-like hydrolase associated with dehalogenase in Enterobacter cloacae MN1 isolated from the contaminated sea-side area of the Philippines - Abdul Hamid, Azzmer Azzar; Nemati, Mahdieh; Abdulghader, Mohamed Faraj; Gicana, Ronie G; Ibtrahim, Nurhafizah; Huyop, Fahrul Zaman (Malaysian Society for Microbiology, 2013)
Aims: The present study aimed at molecular identification of putative Cof-like hydrolase associated with dehalogenase gene from a bacterium that was isolated from a contaminated sea-side area in the Philippines. The bacterium was subjected to 16S rRNA gene sequence analysis for identity of the genus and species. Methodology and results: Based on basic microbiological analysis and 16S rRNA sequence determination, strain MN1 showed high sequence identity to Enterobacter cloacae. This is the first reported study that Enterobacter could degrade 2,2-dichloropropionate (2,2-DCP). A putative dehalogenase gene like was identified by direct sequencing and analysis of the PCR-amplified genomic DNA of the bacterium. A comparative analysis of the sequence data revealed that the amino acid sequence is closely related to several Cof-like hydrolase associated with L-specific dehalogenases. Conclusion, significance and impact of study: Current study may suggest that the hydrolase may have similar function to dehalogenase. However, further analysis like enzyme assay need to be carried out to confirm this. Putative dehalogenase gene can be amplified using PCR technique provided that the specific primers designed were used.